Natural Cooling Techniques For Buildings - Al-Hinai, Hilal Ali Zaher (Cranfield University, 1992)
Modern development in many Third World countries in the hot regions of the world,, have been accompanied by the construction of highly energy-wasteful buildings. The interiors of these buildings have to be mechanically airconditioned in order to achieve thermal-comfort conditions. The consequence of this, has been the rapid increase in electricity-generating plant capacity to match demand (of which, for example at present in Oman, more than 70% nationally is used for air-conditioning modern, energyinefficient buildings). The aim of this work was to find the most suitable way of stabilising or even reducing the electricity demand in a country like Oman. The first step taken to achieve this aim, was to study and draw out lessons from the vernacular architecture of the different climatic regions in Oman. This has been followed by a literature survey that looks at passive and active natural cooling techniques for buildings in hot climates. Mathematical models were then developed to analyze and compare those passive techniques that are most suitable for an environment like that of Oman. Different ways of reducing the heat gain through the roof were investigated and compared. These include the addition of insulation, shading, air-cooling of the roof when the ambient air temperature is lower than that of the roof, and roof ponds. Roof ponds were found to be the most effective of those techniques analyzed. An improved design of the roof pond (the Water Diode roof pond) that eliminates the need for covering the roof pond during the day and uncovering it at night, was suggested and analyzed. The analysis showed promising results. Mathematical models were also developed to analyze and compare dif f erent ways of reducing the heat gain through the walls. These included the use of closed cavities, naturally ventilated cavities, the addition of insulation, and the effect of using brick as compared to concrete block. The analysis suggested that the combination of a Water Diode roof pond and insulated brick wall construction will reduce the heat gain through the envelope of a single room by more than 90%, when compared to a room with un-insulated roof and single-leaf concrete block walls. An empirical validation of the mathematical models was conducted. The results showed a good agreement between the actual and predicted values. An economical analysis of the commonly used roof and wall constructions in Oman, was also conducted. This compared the life-cycle cost of nine different construction techniques, with eight different airconditioning schedules. The result of this analysis showed a clear advantage of using roof insulation, reflective double glazing, and insulated walls with brick outer-leaf and concrete block inner-leaf.